Immunotherapies for hepatocellular carcinoma. (24th December 2021) - Liu, Justin K. H.; Irvine, Andrew F.; Jones, Rebecca L.; Samson, Adel
Abstract: Cases of hepatocellular carcinoma (HCC) are rapidly rising. This is particularly the case in the Western world, as a result of increasing rates of chronic liver disease, secondary to lifestyle‐associated risk factors and the lack of an established screening programme for the general population. Traditionally, radical/curative treatment options for HCC, including liver transplantation and surgical resection are reserved for the minority of patients, presenting with an early stage cancer. For patients with advanced disease, Sorafenib and Lenvatinib were, until recently, the only licensed systemic treatments, and provided only limited survival benefits at the cost of a multitude of potential side effects. Recent scientific advances in the field of cancer immunotherapy have renewed significant interest in advanced HCC, in order to fulfil this apparent area of unmet clinical need. This has led to the success and recent regulatory approval of an Atezolizumab/Bevacizumab combination for the first‐line treatment of advanced HCC following results from the IMbrave150 clinical trial in 2019, with further immune checkpoint inhibitors currently undergoing testing in advanced clinical trials. Furthermore, other cancer immunotherapies, including chimeric antigen receptor T‐cells, dendritic cell vaccines and oncolytic viruses are also in early stage clinical trials, for the treatment of advanced HCC. This review will summarise the major approaches that have been and are currently in development for the systemic treatment of advanced HCC, their advantages, drawbacks, and predictions of where this revolutionary treatment field will continue to travel for the foreseeable future. Abstract : Cancer immunotherapies are emerging as one of the main faces in the new era of cancer treatment and personalised medicine. The cancer immunotherapy pharmaceutical industry is now worth billions of dollars and much research is now focused on harnessing their huge potential in treating a wide range of diseases. In this review, we discuss the different types of cancer immunotherapies currently licensed and in development for the treatment of hepatocellular carcinoma, their drawbacks and limitations, and future innovations that are currently being researched in order to maximise their effectiveness for use in clinical practice.